Silymarin: a potent hepatoprotective agent in poultry industry. Issue 3 (1st September 2017) - Saeed, M.; Babazadeh, D.; Arif, M.; Arain, M.A.; Bhutto, Z.A.; Shar, A.H.; Kakar, M.U.; Manzoor, R.; Chao, S.
Abstract : Silymarin is composed of flavonolignans and derived from the dry seed of milk thistle ( Silybummarianum ) herb. It is used as a hepatoprotective treatment for different liver ailments, mainly cirrhosis, jaundice, growth promotant, alcoholic liver disease, chronic hepatitis C, chronic liver diseases and hepatocellular carcinoma. Reported medicinal properties are anti-inflammatory, immunomodulating, anti-diabetic, antioxidant, low toxicity, promising pharmacokinetics, protective, preventive, regenerative and antifibrotic effects and has been shown to be extremely safe. The mode of action by which silymarin might protect liver cells includes stabilisation of membranes, free radical scavenging, stimulation of hepatocyte protein synthesis and modulation of the immune response. In addition, silymarin can be used to treat jaundice disorders by ameliorating the levels of various hepatic enzymes such as aspartate aminotransferase (AST), alanine aminotransferase (ALT), and alkaline phosphatase (ALP). Moreover, silymarin is able to moderate the immune system, by boosting IL-4, IFN-γ, and IL-10. The hepatoprotective effect of silymarin in poultry farming is poorly understood, although it may be used as a cheap, non-toxic and safe feed additive to manage liver related disorders and to replace synthetic drugs in poultry diets. Hence, this review will allow scientists, veterinarians, researchers, poultry producers to gain a pragmatic edge as well as perspective usage of Silymarin. A main priority is in finding the effective level in poultry whereby it acts as a natural liver tonic in the poultry industry and could reduce veterinary expenses.